Anticancer activity of Neosetophomone B by targeting AKT/SKP2/MTH1 axis in leukemic cells - Shilpa Kuttikrishnan (3520079) (2022)
Neosetophomone B (NSP–B), a meroterpenoid fungal secondary metabolite, was investigated for its anticancer potential in leukemic cell lines (K562 and U937). NSP-B treatment of leukemic cells suppressed cell viability by triggering apoptotic cell death. Apoptosis induced by NSP-B is triggered by mitochondrial signaling and caspase activation. Additionally, NSP-B treatment of leukemic cells causes AKT's inactivation accompanied by downregulation of SKP2 oncogene and MTH1 with a concomitant increase of p21Cip1and p27Kip1. Furthermore, NSP-B causes suppression of antiapoptotic proteins, including cIAP1, cIAP2, XIAP, survivin and BCl-XL. Overall, NSP-B reduces cell viability by mitochondrial and caspase-dependent apoptosis. The inhibition of AKT and SKP2 axis could be a promising therapeutic target for leukemia treatment. Other Information Published in: Biochemical and Biophysical Research Communications License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.bbrc.2022.02.071